2020
DOI: 10.1111/ddi.13025
|View full text |Cite
|
Sign up to set email alerts
|

Nestedness and turnover unveil inverse spatial patterns of compositional and functional β‐diversity at varying depth in marine benthos

Abstract: Aim:The two additive components of β-diversity, namely turnover and nestedness, reflect the two basic mechanisms underlying the overall change in species identities across the landscape, the replacement of species or their loss, respectively.Analogously, functional turnover and nestedness express the replacement or loss of functional traits associated with variations in community composition. However, the extent to which patterns of compositional and functional nestedness and turnover may overlap, or diverge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 84 publications
(149 reference statements)
1
32
0
Order By: Relevance
“…For this to happen, systematic conservation planning should be adopted as the selected decision support tool for the future implementation of the key environmental policies, such as the Habitats, Birds, MSFD and MSP directives (see Table 1). Beyond species and habitat persistence, to better preserve the functioning of marine ecosystems, networks of MPAs should protect the functionality of marine communities and ecosystems (Bevilacqua and Terlizzi, 2020). To do so, identifying which habitats and species support fundamental ecological roles through space and time is needed.…”
Section: Improved Conservation Planningmentioning
confidence: 99%
“…For this to happen, systematic conservation planning should be adopted as the selected decision support tool for the future implementation of the key environmental policies, such as the Habitats, Birds, MSFD and MSP directives (see Table 1). Beyond species and habitat persistence, to better preserve the functioning of marine ecosystems, networks of MPAs should protect the functionality of marine communities and ecosystems (Bevilacqua and Terlizzi, 2020). To do so, identifying which habitats and species support fundamental ecological roles through space and time is needed.…”
Section: Improved Conservation Planningmentioning
confidence: 99%
“…The nestedness component reflects changes in species richness caused by selective species loss or gain that may be associated with recent vicariance events, e.g., insular changes by sea‐level rise (Rijsdijk et al, 2014), or a colonization lag after drastic environmental changes such as ice age disturbances (Hortal et al, 2011). Therefore, each component is expected to have an independent relationship with geographical and environmental distance (Antão et al, 2019; Bevilacqua & Terlizzi, 2020), and their relative importance may change depending on historical habitat stability (Baselga et al, 2012). The turnover component can be expected to have a steep slope and an asymptotic relationship with spatial distance under strong dispersal limitation, while a flatter relationship would be observed when dispersal limitation is weak or absent (Gómez‐Rodríguez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2019) also found that local and regional drivers (e.g., altitude, TN concentration, TP concentration) contribute to structuring species and functional beta diversity patterns (mainly due to species turnover and functional nestedness). However, when environmental factors change dramatically from suitable to extreme conditions, some tolerant species will be screened out to form nested communities (Bevilacqua & Terlizzi, 2020; da Silva et al., 2018). This process (turnover and nestedness driven by environmental factors) is in line with the catastrophic regime shifts that occur in shallow lakes, that is, when the water environment conditions change drastically, the structure, function, and stability of freshwater ecosystems also change (Scheffer & Carpenter, 2003; Scheffer et al., 2001).…”
Section: Discussionmentioning
confidence: 99%